Development Conceptual and Empirical Validity of Collaboration and Communication Skills Instruments in Sports Learning - Endang Sri Estimurti; yuni pantiwati; Latipun Latipun; Bulkani Bulkani (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The importance of 21st-century skills, especially collaboration and communication skills, is increasingly emphasized in the era of globalization and the Industrial Revolution 4.0. However, there is a gap in measuring these skills in Indonesia's sports education context. This research aims to develop and validate a new instrument to measure collaboration and communication skills in sports learning effectively. Exploratory and Confirmatory Factor Analysis was used to identify and validate collaboration and communication skills factors. This research involved 510 students from Palangkaraya, Lamandau, Seruyan, Pulang Pisau, Kapuas, Buntok, Sampit, and Murung Raya with a total of 8 regions in Indonesia. The research results show that the instrument developed has good validity and reliability. Evaluation of scale characteristics and confirmatory factor analysis demonstrated the reliable quality of the instrument for measuring collaboration and communication skills in the context of sports learning. Through the development of this instrument, it is hoped that it can significantly contribute to the understanding of collaboration and communication skills in sports learning in Indonesia. Hopefully, this instrument will become a valuable tool for educators, researchers, and practitioners to measure and develop these skills and provide a basis for improving the quality of sports education in Indonesia.